Magnetic Hyperthermia: Unlocking the Potential of Magnetotactic Bacteria as Magnetic Hyperthermia Agents (Small 41/2019). Issue 41 (8th October 2019) - Gandia, David; Gandarias, Lucía; Rodrigo, Irati; Robles‐García, Joshua; Das, Raja; Garaio, Eneko; García, José Ángel; Phan, Manh‐Huong; Srikanth, Hariharan; Orue, Iñaki; Alonso, Javier; Muela, Alicia; et al.
Abstract : In article number 1902626, Javier Alonso, Alicia Muela, M a Luisa Fdez‐Gubieda, and co‐workers show how magnetotactic bacteria, microorganisms that biomineralize chains of magnetic nanoparticles (magnetosomes), present high potential as magnetic hyperthermia agents for cancer treatment: the chain structure is perfect for enhancing the heating efficiency (specific absorption rate), and the bacteria can be internalized by human lung carcinoma cells for hyperthermia treatment.